Platform Governance and the “Infodemic” - Siapera, Eugenia (Javnost-The Public, 2022)
This article discusses the dominant metaphor of infodemic, the role of platforms and their policies. In understanding the spread of Covid-19 misinformation as an informational epidemic, we are led to construct the problem as one of viral spread. Virality, however, has been conceptualised as a key attribute of social media platforms. A tension therefore emerges between to encouraging good virality while limiting bad virality. To examine how platforms have dealt with this , the article analyses the policies of two platforms, Facebook and YouTube, alongside the EU Code of Practice which they have both signed. The analysis reveals that they focus on the circulation of mis/disinformation, developing an apparatus of security around it. This consists of a set of strategies, techno-material tools for the enforcement of the strategies, measures for disciplining users, and procedures for legitimating and re-adjusting the whole apparatus. However, this apparatus is not fit for the purpose of addressing mis/disinformation for two reasons: firstly, its primary objective is to sustain the platforms and not to resolve the problem of mis/disinformation; secondly it obscures the question of production of mis/disinformation. Ultimately, addressing mis/disinformation in a comprehensive manner requires a more thorough and critical social inquiry.